Strategi Penanaman Nilai-nilai Pendidikan Anti Korupsi di Pondok Pesantren - Rosyada, Faiz Alim (ILUMINASI: Journal of Research in Education, 2024)
This research aims to describe the anti-corruption education values that are instilled in students at Islamic boarding schools and the strategies used to instill anti-corruption education values in students. The approach used in this research is qualitative with descriptive research type. Data collection techniques use interview and observation methods. Informants were selected through purposive sampling technique. Data were analyzed using the interactive model from Miles and Huberman. The research results show that the students have been instilled with anti-corruption values in the form of honesty, independence, social care, hard work, cooperation, responsibility, discipline, simplicity, courage, justice and piety. Anti-corruption values are instilled through verbal communication carried out during learning activities and outside of it. habituation through religious, educational and social activities and so on. as well as the cultural conditioning of Islamic boarding schools which is controlled by caregivers and student management organizations.